Current medical diagnosis & treatment 2014 - McPhee, Stephen J.; Papadakis, Maxine A.; Therapeutics (New York : McGraw-Hill Education, 2013)
Provides information on the signs, symptoms, epidemiology, etiology, and treatment of more than one thousand diseases and disorders; and includes drug treatment tables, color plates, NAEPP asthma guidelines, and other resources.
Chapter 1. Disease prevention & health promotion -- Chapter 2. Common symptoms -- Chapter 3. Preoperative evaluation & perioperative management -- Chapter 4. Geriatric disorders -- Chapter 5. Palliative care & pain management -- Chapter 6. Dermatologic disorders -- Chapter 7. Disorders of the eyes & lids -- Chapter 8. Ear, nose, & throat disorders -- Chapter 9. Pulmonary disorders -- Chapter 10. Heart disease -- Chapter 11. Systemic hypertension -- Chapter 12. Blood vessel & lymphatic disorders -- Chapter 13. Blood disorders -- Chapter 14. Disorders of hemostasis, thrombosis, & antithrombotic therapy -- Chapter 15. Gastrointestinal disorders -- Chapter 16. Liver, biliary tract & pancreas disorders -- Chapter 17. Breast disorders -- Chapter 18. Gynecologic disorders -- Chapter 19. Obstetrics & obstetric disorders -- Chapter 20. Rheumatologic & immunologic disorders -- Chapter 21. Electrolyte & acid-base disorders -- Chapter 22. Kidney disease -- Chapter 23. Urologic disorders -- Chapter 24. Nervous system disorders -- Chapter 25. Psychiatric disorders -- Chapter 26. Endocrine disorders -- Chapter 27. Diabetes mellitus & hypoglycemia -- Chapter 28. Lipid disorders -- Chapter 29. Nutritional disorders -- e1. Anti-infective hemotherapeutic & antibiotic agents -- Chapter 30. Common problems in infectious diseases & antimicrobial therapy -- Chapter 31. HIV infection and AIDS -- Chapter 32. Viral & rickettsial infections -- Chapter 33. Bacterial & chlamydial infections -- Chapter 34. Spirochetal infections -- Chapter 35. Protozoal & helminthic infections -- Chapter 36. Mycotic infections -- Chapter 37. Disorders related to environmental factors -- Chapter 38. Poisoning -- Chapter 39. Cancer -- e2. Fundamentals of human genetics -- Chapter 40. Clinical genetic disorders -- Chapter 41. Sports medicine & outpatient orthopedics -- Chapter 42. Women's health issues -- e3. Diagnostic testing & medical decision making -- e4. Information technology in patient care -- e5. Integrative medicine -- Appendix: Therapeutic drug monitoring, & laboratory reference intervals
A Lange medical book--title page
Includes bibliographical references and index
Keywords: Provides information on the signs, symptoms, epidemiology, etiology, and treatment of more than one thousand diseases and disorders; and includes drug treatment tables, color plates, NAEPP asthma guidelines, and other resources; Diagnosis; Therapeutics